Faktor-Faktor Pembentukan Karakter berdasarkan Amsal 13:22 tentang Warisan Harta dan Ajaran Moral - Farel Yosua Sualang; Eden Edelyn Easter (Sekolah Tinggi Teologi Jaffray Jakarta, 2020)
This article describes “the factors of character building based on Proverbs 13:22 on inheritance and moral teachings.” The uniqueness of the book of Proverbs is that besides discussing the importance of the relationship between God and humans, it also shows the importance of Character Building. The analysis of this scientific work uses the research method of Wisdom Hermeneutics, which uses literal, context, structural and figurative analysis. The nature of a righteous person deserves to bequeath property to children / other people to obtain inheritance rights. Robert Williamson provides an interpretation of Proverbs 13:22 by emphasizing the habit of experience as the main factor in character building, while Mark Rathbone finds that the family/community factor is a habit /culture in the interpretation of Proverbs 13:22. But from the other side, this article shows that the Interpretation of Proverbs 13:22 discover 4 factors for character building regarding inheritance and moral teachings, namely: Personality Factors, Life Example, Communication and Financial Literacy. Where these factors are passed from one generation to another.